2006
DOI: 10.1162/jocn.2006.18.10.1712
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation Dissociates Working Memory Manipulation from Retention Functions in the Prefrontal, but not Posterior Parietal, Cortex

Abstract: Abstract& Understanding the contributions of the prefrontal cortex (PFC) to working memory is central to understanding the neural bases of high-level cognition. One question that remains controversial is whether the same areas of the dorsolateral PFC (dlPFC) that participate in the manipulation of information in working memory also contribute to its short-term retention (STR). We evaluated this question by first identifying, with functional magnetic resonance imaging (fMRI), brain areas involved in manipulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 50 publications
(57 reference statements)
11
101
0
3
Order By: Relevance
“…Previous functional neuroimaging studies had reported peaks of increased activity in both the IPS and MDLFC regions (i.e., the frontoparietal network) during the performance of alphabetization (Collette et al, 1999;Postle et al, 2006), letter-number sequencing (Emery et al, 2008), and digit backward tasks (Gerton et al, 2004;Sun et al, 2005). In retrospect, all these working memory tasks can be seen as requiring some form of manipulation of the stimuli in working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous functional neuroimaging studies had reported peaks of increased activity in both the IPS and MDLFC regions (i.e., the frontoparietal network) during the performance of alphabetization (Collette et al, 1999;Postle et al, 2006), letter-number sequencing (Emery et al, 2008), and digit backward tasks (Gerton et al, 2004;Sun et al, 2005). In retrospect, all these working memory tasks can be seen as requiring some form of manipulation of the stimuli in working memory.…”
Section: Discussionmentioning
confidence: 99%
“…A second is that this activity may represent any of a number of other functions that have been ascribed to the PFC and that might be sensitive to variations in load. These include, but are not limited to, deploying selective attention (Passingham and Sakai, 2004) (Chao and Knight, 1998;Postle, 2005) generated interference, manipulating the contents of WM toward achieving behavioral goals (Owen et al, 1996;Postle et al, 2006), and maintaining a representation of task rules and/or other information critical for the flexible control of behavior (Miller and Cohen, 2001;Bunge et al, 2003;Hon et al, 2006). Regardless of which of these conceptualizations is to be preferred, an important question for future research will be whether individual differences in WM capacity or some other "trait" might predict which subjects do or do not recruit MFG during performance of delayed-recognition tasks (Rypma et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The first group of relevant studies [18][19][20][21][22] aimed to verify the hypothesis that the DLPFC plays a crucial role in WM by using the TMS technique. All the studies agree in finding that the DLPFC is involved in the performance of WM tasks, in particular those tasks in which the manipulation of information is required.…”
Section: Wm and Tmsmentioning
confidence: 99%
“…Moreover, Mottaghy and others [20][21][22] investigated the chronometry of the DLPFC involvement in WM and reported how TMS really interferes with the WM task if applied later than 180 ms after the stimulus onset. in fact, they found that the processing of information in WM follows a flow from posterior to anterior regions, and from right to left hemisphere within the PFC [20] .…”
Section: Wm and Tmsmentioning
confidence: 99%